2010
DOI: 10.1093/jac/dkq177
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of T-2307, a novel arylamidine, in Candida albicans

Abstract: The considerably higher concentrations of T-2307 were selectively accumulated in C. albicans via transporter-mediated systems, as compared with the concentrations in rat hepatocytes. This transporter-mediated uptake of T-2307 contributes to its potent anticandidal activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 28 publications
1
29
0
2
Order By: Relevance
“…Since the affinity of pentamidine for these transporters is low, the difference in in vitro antifungal activity between T-2307 and pentamidine may be due to the difference in the uptake rate. We also confirmed that T-2307 is incorporated by C. albicans with approximately 130 times higher concentration than that by mammalian cells (19). T-2307 showed marked selectivity for C. albicans over mammalian cells regarding in vitro growth inhibition (data not shown).…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…Since the affinity of pentamidine for these transporters is low, the difference in in vitro antifungal activity between T-2307 and pentamidine may be due to the difference in the uptake rate. We also confirmed that T-2307 is incorporated by C. albicans with approximately 130 times higher concentration than that by mammalian cells (19). T-2307 showed marked selectivity for C. albicans over mammalian cells regarding in vitro growth inhibition (data not shown).…”
Section: Resultssupporting
confidence: 71%
“…We considered that this disconnect may be because T-2307 is actively accumulated by cells. It has been reported that T-2307 is concentrated approximately 5,000-fold from the extracellular medium by C. albicans cells (19). In our preliminary experiments, T-2307 at 10 M significantly collapsed the membrane potential of mitochondria isolated from C. albicans.…”
Section: Resultsmentioning
confidence: 43%
See 1 more Smart Citation
“…7 -9 In our previous study, we characterized the uptake of T-2307 in C. albicans. 10 T-2307 was concentrated into C. albicans cells from the extracellular medium at .3000-fold above the extracellular concentration. The accumulation was approximately two orders of magnitude greater than that achieved with rat hepatocytes.…”
Section: Introductionmentioning
confidence: 99%
“…We had previously reported that T-2307, a novel arylamidine, exhibits broad-spectrum in vitro and in vivo antifungal activity against clinically significant pathogens (7,8,16). The analogous arylamidine derivatives, such as pentamidine and DB75, exhibit antiprotozoan activities against Plasmodium, Trypanosoma, and Leishmania (2,3,14).…”
mentioning
confidence: 99%